Tuhan, Manusia dan Alam dalam Perspektif Filsafat Islam - Ruslan, Ruslan (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2018)
This paper aims to find answers to the concepts of God, humans, and nature in the perspective of the philosophy of Islamic education and relations between the three. The Lord concluded with the concept of Tauhid. In this concept, nature and its contents include here humans must serve and worship only to Him. Whereas the nature of human beings is divided into three concepts, namely first al-Basyar, the second al-Insan, and the third al-Nas which shows humanity in total without referring to his faith or disbelief status. Meanwhile, nature was created by Allah SWT as a medium of education for humans. Armed with its potential, humans can learn everything in this nature for the benefit of life and human life. The relationship between God, humans and nature is always associated with the concept of khalifah and 'Abd Allah. Keywords: God, human, nature, Philosophy of Islamic Education